Evaluation of Hydroalcoholic Extract of Convolvulus pluriculis (Shankapushpi) for Standardization by Colorimetric Method: A Preliminary Report - Swamy, Gangadhara; Holla, Rajendra; Rao, Suresh R. (Journal of Health and Allied Sciences NU, 2019)
Aim This study was aimed to evaluate the hydroalcoholic extract of Convolvulus pluricaulis (HACP) for standardization using colorimetric method.Materials and Methods Establishment of standardization for the Ayurvedic formulations is most important for its chemical compounds, biological action, and its quality reassurance in production and manufacturing of traditional herbal medicines. As most of the drugs are standardized, drug companies are using substitute drugs instead of true drugs. So to make finest superiority drugs, it is necessary to validate the raw drugs. Observing the existing trend in mind, HACP was subjected to standardize procedures for the phytochemical tests. The separation of the bioactive substances from the HACP was performed using both manual methods and high-profile thin-layer chromatography (HPTLC).Results From this study, it is revealed that the seed contains alkaloids, carbohydrates, steroids, tannins, terpenoid, and phenol which gave the medicine numerous therapeutic properties.Conclusion The study was rapid, reproducible, and could be used for routine monitoring of various biological properties of HACP.
Keywords: hydroalcoholic; Convolvulus pluriculis; phytochemical analysis; HPTLC